PERAN PEER GROUP DALAM MELAKUKAN DETEKSI DINI MELALUI PEMERIKSAAN PAYUDARA SENDIRI (SADARI) SEBAGAI UPAYA PENCEGAHAN KANKER PAYUDARA PADA REMAJA - Riski Akbarani; Eva Inayatul Faiza (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2022)
Ensuring healthy lives and promoting well-being for all at all ages by 2030 is the third Target of the SDGs. The target includes efforts to reduce the incidence of deaths from non-communicable diseases including breast cancer. The incidence of breast cancer increases with age, but we can prevent this cancer and if it is detected early, we will get better treatment. Early detection through BSE which is carried out starting at the age of adolescence with increased vigilance and is believed to reduce the number of deaths due to breast cancer. The motivation of young women in doing BSE is different, through peer groups it is expected that there will be changes in health behavior in young women. The expected behavior is that young women are able to carry out early detection of breast cancer through breast self-examination. The general purpose of this study was to determine the role of peer groups in conducting early detection through breast self-examination (BSE) as an effort to prevent breast cancer. This research is a quasi experimental research with pre test and post test with control group design. The sampling technique was purposive sampling. Collecting data using a questionnaire through a google form and a checklist. The tools used to train peer groups are training modules. The data processing steps are editing, coding, and data entry. Analysis using the Paired Sample T-test with a significance result of 0.000 < (α) 0.05. This shows that there is a significant difference between the average scores before and after being given health education about breast cancer. So it can be concluded that there is a significant increase in respondents' BSE skills after receiving peer education using video media and teaching aids. the influence of peer education on the practice skills of BSE in adolescent girls. Peer youth educators are considered to have more influence on BSE abilities than teachers. Active learning methods provided by peer educators can improve the ability of adolescent self-awareness.